OPTIMALISASI PERAN KADER POSYANDU DALAM MENINGKATKAN KEMANDIRIAN GIZI DAN KESEHATAN UNTUK MENCEGAH HIPERTENSI PADA LANSIA DI DESA SUSUKAN KECAMATAN SUMBANG KABUPATEN BANYUMAS - Saryono; Anas Sumeru; Atikah Proverawati (Unit Penelitian dan Pengabdian Masyarakat, Politeknik Banjarnegara, 2018)
Hypertension has a very high prevalence in the world. Problems in hypertension are generally ignored and not considered a risk of death, even though uncontrolled hypertension is very dangerous, so prevention efforts are very important to emphasize. The purpose of this article is to describe the efforts to optimize the role of health posyandu cadres in increasing nutritional and health independence to prevent hypertension in Susukan Village, Sumbang District, Banyumas Regency. The subject of treatment was a group of posyandu cadres in Susukan village, Sumbang sub-district, Banyumas regency. This health intervention study uses one group pre and post test design. The treatment were consisted of increasing knowledge about hypertension, training in early detection of hypertension, modification of low-salt foods according to the nutritional needs of the elderly, and preparation of food menus for elderly hypertensive people that made from local food. Before and after treatment, the respondent's understanding was evaluated with a knowledge level questionnaire and early detection ability was assessed qualitatively. The results showed that the level of knowledge of cadres about hypertension, and early detection skills by carrying out blood pressure checks increased significantly. The conclusion of this study is that the mentoring model is effective in optimizing the role of Posyandu cadres to improve nutrition and health independence to prevent hypertension in the elderly.